Using Diary in Improving Students' Grammar Ability - Pratama, rizky Mirani Desi (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2023)
Grammar is the teaching and learning of grammar. Grammar helps us in several phenomena. For example, if we want to translate a sentence into English or vice versa, we need grammar so that the meaning of the sentence is clear and easy to understand. Grammar is also one aspect of language that is difficult to teach. Therefore, the teacher must have a solution so that learning grammar becomes more interesting and easy to understand. The teacher must have some good grammar teaching techniques, especially the past tense. A study to determine the effectiveness of teaching English Past Tense through the diary writing technique was conducted in the third grade of an elementary school in Bogor. Data collection was carried out through observation, interview, teaching and learning process, pre-test and post-test. The implementation of the technique is that students must write down their activities that they have done. Then the results of their writing will be analyzed together. Using this technique makes it easier for the students to understand and use the past tense correctly. Students can also do a post-test which is a means to evaluate teaching and learning techniques and processes properly and to be more active in the teaching and learning process. The post-test results show that teaching English past tense through diary writing technique is a good solution to improve students' understanding of past tense.